Uptake of Copper and Zinc in Lettuce (Lactuca sativa L.) Planted in Sida Soil and Lignite Bottom Ash Mixtures - Silapanuntakul, Suthep; Intrarasaksit, Prat; Vatanasomboon, Pisit; Tantrakarnapa, Kraichat (Naresuan University Journal: Science and Technology (NUJST); Vol 25 No 3 (2017): July - September 2017, 2017)
Attempts to mitigate the environmental problems from heavy metal contaminated wastes by phytoremediation technique have been intensively investigated.  This research was conducted to determine the physical and chemical characteristics of mixture materials (Sida soil mixed with lignite bottom ash), and uptake of copper and zinc in lettuce ( Lactuca sativa L .) parts cultivated under laboratory conditions.  The effect of copper and zinc on lettuce yields was also investigated.      Results indicated that the pH value of mixtures ranged from 6.64±0.78 to 6.89±0.98. The percentage of moisture content and organic content ranged from 10.22±0.24 to 11.85±0.54 % . and 1.86±0.85to 5.04±0.38 %, respectively.  Amount of nitrogen, phosphorus and potassium ranged from 0.31±0.03to 0.45±0.04 %, 0.45±1.35 to 0.56±1.94 %, and 0.92±0.01 to 0.94±0.03 %. In addition, the mixture contained copper and zinc ranging from 13.12±1.71to 26.13±2.30mg/kg, and 66.84±5.84to 137.74±4.13 mg/kg, respectively.  It was noted that copper and zinc accumulation in mixture ratios showed a significant difference as the amount of lignite bottom ash in mixture ratios increased (P<0.05).  The highest copper and zinc accumulation was found at mixture ratio of 0.6:0.4 in lettuce root (21.46 ± 5.90 mg/kg and 113.47 ± 4.13 mg/kg), followed by lettuce leaf (8.18 ± 1.20 mg/kg and 32.94 ± 7.34 mg/kg).  The accumulation of both heavy metals in root and leaf of lettuces significantly related to the increasing of lignite bottom ash ratios (P<0.05). In addition, the highest lettuce yield was found at a ratio of 0.8:0.2 (1.43 ± 0.06 g/plant) and 0.6:0.4 (1.43 ± 0.03 g/plant).   A significant difference in lettuce yield with the increased lignite bottom ash mixtures ranging from 0.9:0.1 to 0.6:0.4 was observed (P<0.05).  The results suggest that lignite bottom ash mixtures can be used as supplementary micronutrients in soil for plants and planted lettuce at mixture ratios of 9:1, 8:2 and 7:3 are not harmful for consumers since the accumulation of both heavy metals was within the Criteria of Food and Drug Administration (copper not exceeded 20 mg/kg and zinc not exceeded 100 mg/kg).  Also, this plant have a potential use of phytoremediation to treat the copper and zinc contaminated land but further investigation is still required. Keywords: lettuce, lignite bottom ash, Sida soil, copper and zinc uptake, phytoremediation
Keywords: lettuce, lignite bottom ash, Sida soil, copper and zinc uptake, phytoremediation